Ethylene Production by Root Nodules and Effect of Ethylene on Nodulation in Glycine max - Hunter, William J. (1993)
Nodulated soybean roots produced more ethylene and contained more 1-aminocyclopropane-1-carboxylic acid than uninoculated roots. Nodules produced more ethylene and contained more 1-aminocyclopropane-1-carboxylic acid per gram of material than roots. Almost all of the ethylene produced by the nodules was produced by the plant fractions of the nodules. Ethylene, at physiological concentrations, did not inhibit nodulation in soybeans.